EFFECT OF DRIP IRRIGATION AND SUBSURFACE DRIP IRRIGATION SYSTEM ON YIELD AND YIELD COMPONENTS OF CORN - & et al., Abdul-Razak (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
A field experiment was conducted at the experimental farm of Field Crops Sciences Department, College of Agriculture, University of Baghdad, during the spring season of 2013وto investigate the effect of Irrigation method Drip Irrigation (DI) and subsurface Drip Irrigation (SDI) and system operational pressure on yield and yield’ components and on water use efficiency (WUE) of corn (Zea mays L.) Var. Buhoth 5018. The experiment was laid out as a split plot in randomized complete block design (RCBD) with three replication. The system operational pressure (P) of 3 levels ( 30,50, and 70 kpa) were used as main plots called as P1 , P2 and P3 respectively, and Irrigation methods (DI and SDI) were used as sub plots. Data showed that the use of SDI resulted in a highest yield rate per unit area (8.88m ton.ha-1) with 2.3% comparing with surface drip Irrigation (DI), It’s also caused a significant increase in number of studied traits such as; soil volumetric moisture content by2%, ear length by 11.4%, ear high 7.9%, number of seeds per row by 11.7%, and wt. of 100 seeds by 3.5%. However, data showed a significant increase caused by rising the system Operational pressure (P) on yield, as highest (P3) increase yield by 6.5% in comparison with 30 kpa, and on all of the following measured characteristics such as volumetric moisture content by 5.5%, water uniformity distribution 2.5%( reaching 97.62%), Ear length by 11.7%, Ear high by 41.6%, number of seed rows by 17.2%, number of seeds per row by 123.4%, and wt. of 100 seeds by 19.3%. Water Use Efficiency (WUE) was improved by 2.2% by using the SDI with 70 kpa by 6.8%, concluding that using SDI with 70Kpa in a system pipe lines pleased at 0.20m below soil surface can be recommended in corn fields at central